Mycobacterium smegmatis GlnR Regulates the Glyoxylate Cycle and the Methylcitrate Cycle on Fatty Acid Metabolism by Repressing icl Transcription - Qi, Nan; She, Guo-Lan; Du, Wei; Ye, Bang-Ce (Frontiers in Microbiology, 2021)
Mycobacterium smegmatis (Msm), along with it’s pathogenic counterpart Mycobacterium tuberculosis (Mtb), utilizes fatty acids and cholesterol as important carbon and energy sources during the persistence within host cells. As a dual-functional enzyme in the glyoxylate cycle and the methylcitrate cycle, isocitrate lyase (ICL, encoded by icl or MSMEG_0911) is indispensable for the growth of Msm and Mtb on short-chain fatty acids. However, regulation of icl in mycobacteria in response to nutrient availability remains largely unknown. Here, we report that the global nitrogen metabolism regulator GlnR represses icl expression by binding to an atypical binding motif in the icl promoter region under nitrogen-limiting conditions. We further show that GlnR competes with PrpR, a transcriptional activator of icl, and dominantly occupies the co-binding motif in the icl promoter region. In the absence of GlnR or in response to the excess nitrogen condition, Msm cells elongate and exhibit robust growth on short-chain fatty acids due to the PrpR-mediated activation of icl, thereby inducing enhanced apoptosis in infected macrophages. Taken together, our findings reveal the GlnR-mediated repression of icl on fatty acid metabolism, which might be a general strategy of nutrient sensing and environmental adaptation employed by mycobacteria.